The evolving epidemiology of rotavirus A infection in Brazil a decade after the introduction of universal vaccination with Rotarix® - Carvalho-Costa, Filipe A. (BMC Pediatr, 2019)
BACKGROUND: Brazil introduced the monovalent rotavirus vaccine (Rotarix®) in 2006. This study aimed to assess the epidemiology and genotype distribution of species-A rotavirus (RVA) in Brazil, comparing the pre- and post-vaccination periods. METHODS: Laboratory-based RVA surveillance included 866 municipalities in 22 Brazilian states, over a 21-year period. A total of 16,185 children with diarrheal diseases (DD) aged up to 12 years between 1996 and 2005 (pre-vaccination period, n = 7030) and from 2006 to 2017 (post-vaccination period, n = 9155) were enrolled. RVA was detected using ELISA immune assay and/or polyacrylamide gel electrophoresis and genotyped using nested PCR and/or nucleotide sequencing. RVA-positivity and genotypes detection rates were compared in distinct periods and age groups and Rotarix vaccination status. RESULTS: RVA-positivity in pre- and post-vaccination periods was, respectively: 4–11 months bracket, 33.3% (668/2006) and 16.3% (415/2547) (p <  0.001); 12–24 months, 28.2% (607/2154) and 22.2% (680/3068) (p <  0.001); 25–48 months, 17.4% (215/1235) and 29.4% (505/1720) (p <  0.001). Genotypes distribution in the pre- and post-vaccination periods was, respectively: G1P [8]/G1P[Not Typed], 417/855 (48.8%) and 118/1835 (6.4%) (p <  0.001); G2P [4]/G2P[NT], 47/855 (5.5%) and 838/1835 (45.7%) (p <  0.001); G3P [8]/G3P[NT], 55/855 (6.4%) and 253/1835 (13.8%) (p <  0.001); G9P [8]/G9P[NT], 238/855 (27.8%) and 152/1835 (8.3%) (p <  0.001); G12P [8]/G129P[NT], 0/871 (0%) and 249/1835(13.6%) (p <  0.001). Concerning infants aged 4–11 months, RVA frequency in fully vaccinated and non-vaccinated individuals was 11.9% (125/1052) and 24.5% (58/237) (p <  0.001), respectively. In children aged 12–24 months, RVA detection rate was 18.1% (253/1395) and 29.6% (77/260) (p <  0.001), for the vaccinated and non-vaccinated individuals, respectively (p <  0.001). CONCLUSIONS: RVA infection was significantly less frequent in children aged ≤2 years with DD after implementing vaccination, mainly among vaccinated children. It was also observed a decrease of P [8] circulation and emergence of G2P[4] in 2005, and afterwards in the post-vaccine era, with spreading of G12P[8] in 2014–2015 and of G3P[8] in 2017. Continuous RVA surveillance must be carried out in this scenario.